Study of shadowing effect by aircraft maneuvering for air-to-ground communication - Meng, Yu Song (2013)
This paper investigates the shadowing effect induced by an aircraft during maneuvering for air-to-ground communication at C band. Narrowband measurements with a linear flight route and a circular flight route have been conducted and the results are compared in this paper. It is found that, the communication link can easily be shadowed by the aircraft body. Due to this shadowing, the transmitted signal undergoes significant attenuation of up to 28 dB at 5.7 GHz. Results also show that spatial diversity at the ground station is unable to eliminate this shadowing effect caused by the aircraft during maneuvering.